Photodegradation of oxytetracycline using fluorescent light driven ZnO quantum dots synthesised via microwave method - Jasni, Normawati; Iqbal, Anwar; Abu Bakar, Noor Hana Hanif; Wan Ahmad Kamil, Wan Maryam; Danial, Wan Hazman; Ismail, Mohamad Wafiuddin; Rajappan, Kalaivizhi (Penerbit Universiti Sains Malaysia, 2023)
In this study, Li+ ions capped zinc oxide quantum dots (ZnO QDs) was synthesised using the microwave method. The X-ray diffraction (XRD), transmission electron microscopy (TEM), high-transmission electron microscopy (HR-TEM), scanning electron microscopy (SEM), UV–Visible diffuse reflectance spectroscopy (UV-DRS), and photoluminescence (PL) techniques were used to characterise the structural, morphological, optical properties of the ZnO QDs. The XRD analysis reveals that ZnO QDs have a hexagonal wurtzite structure with an average crystallite size of 9.9 nm. The morphology of ZnO QDs was observed to be quasi-spherically shaped with an average particle size of 10 nm. The PL analysis detected the presence of various defects. All these factors enhanced the photodegradation of oxytetracycline (OTC) under fluorescent light irradiation. Within 40 min, 88.3% of OTC was removed, which was higher compared to the bulk ZnO reported in the literature. This technology is aimed at small animal husbandries due to the photocatalyst synthesis method’s simplicity and the photocatalysis process’s requirements.